Reduced Number and Activity of Circulating Endothelial Progenitor Cells in Acute Aortic Dissection and Its Relationship With IL-6 and IL-17 - Huang, Zhenhua; Liu, Zhihao; Wang, Keke; Ye, Zi; Xiong, Yan; Zhang, Bin; Liao, Jinli; Zeng, Lijing; Zeng, Haitao; Liu, Gexiu; Zhan, Hong; Yang, Zhen (Frontiers in Cardiovascular Medicine, 2021)
To investigate the number and function of peripheral endothelial progenitor cells in patients with aortic dissection, comparedwith hypertensive patients and its possible mechanism.35 patients with acute aortic dissection (AAD)and 20 patients with primary hypertensionwere involved．Flow cytometry analysis was used to detect the number of CD34+/KDR+cells, known as circulating endothelial progenitor cells in the two groups, and acetylated low density lipoprotein (ac-LDL) and lectin fluorescent staining method were appliedto testthe number of cultured endothelial progenitor cells. In addition, the migration and proliferation of endothelial progenitor cells were measuredrespectively with MTT and Transwell method.Finally, interleukin 6 (IL-6) and interleukin 17 (IL-17) level wereinvestigated by enzyme-linked immunosorbent assay (ELASA).The number of circulating EPCs in AAD group was significantly lower than that in hypertensivegroup, and the migration and proliferation of circulating EPCs in AAD group were remarkedlyreducedthan that in hypertensivegroup. In addition, the decrease in number,migrationand proliferation ofcirculating EPCs were significantly inversecorrelationwith the aortic dissection detection risk score (ADD-RS). More importantly,significant increase in plasma IL-6 and IL-17 level was found to be in the AAD group and the two inflammatory factors were inversely correlated with the number, migrationand proliferation ofcirculating EPCsin the AAD group. we firstly demonstrated that the reduced number and functionof circulating EPCswere found in the AAD group, which was partly explained by the mechanism that IL-6 and IL-17 were up-regulated in the AAD and sequentially, down-regulated the number, migration and proliferation of circulating EPCs.